ELECTROCARDIOGRAPHY METHOD FOR DETECTING SIGNS OF CARDIOVASCULAR DISEASE - Qobiljonova Shaxnoza Rustam qizi; Tog’ayeva Gulchiroy Oybek qizi; Soataliyeva Ruxshonabonu Sherzod qizi; Salimova Shahina Farmon qizi (Modern American Journals, 2025)
Cardiovascular diseases (CVD) remain one of the leading causes of death worldwide. Effective diagnosis and early detection of cardiac pathologies are key factors in reducing the risk of complications and improving patients' quality of life. One of the most common, accessible, and informative methods of cardiac examination is electrocardiography (ECG). This method records the electrical activity of the heart and can detect a wide range of conditions, from arrhythmias to ischemic processes.